2008
DOI: 10.1007/s11295-007-0131-z
|View full text |Cite
|
Sign up to set email alerts
|

Md-ACS1 and Md-ACO1 genotyping of apple (Malus x domestica Borkh.) breeding parents and suitability for marker-assisted selection

Abstract: Fruit ethylene production genotypes for Md-ACS1 and Md-ACO1 were determined for 60 apple cultivars and 35 advanced breeding selections. Two alleles for each gene are commonly found in cultivated apple. Earlier studies showed that genotypes homozygous for the ACS1-2 allele produce less ethylene and have firmer fruit than ACS1-1/2 and ACS1-1/1 genotypes. ACO1 plays a minor role compared to ACS1, with homozygous ACO1-1 having lower ethylene production. In this study, ACS1-2 and ACO1-1 homozygotes had firmer fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 31 publications
7
63
0
4
Order By: Relevance
“…Interestingly, apples and peaches do not respond the same when 1-MCP, an ethylene blocker, is applied (Cin et al 2006 ) indicating that these systems differ signifi cantly as does their postharvest competence. With apples, various allelic forms of ACO and ACS have been characterized across cultivars, and the allelic states that condition the best fi rmness have been identifi ed with molecular markers opening up the possibility of using these in the selection for better postharvest quality in apple Oraguzie 2010 ;Zhu and Barritt 2008 ) .…”
Section: Firmness and Postharvest Competencementioning
confidence: 99%
“…Interestingly, apples and peaches do not respond the same when 1-MCP, an ethylene blocker, is applied (Cin et al 2006 ) indicating that these systems differ signifi cantly as does their postharvest competence. With apples, various allelic forms of ACO and ACS have been characterized across cultivars, and the allelic states that condition the best fi rmness have been identifi ed with molecular markers opening up the possibility of using these in the selection for better postharvest quality in apple Oraguzie 2010 ;Zhu and Barritt 2008 ) .…”
Section: Firmness and Postharvest Competencementioning
confidence: 99%
“…While 1-MCP treatment inhibited the deterioration of fruit quality, its effect on the inhibition of internal ethylene contents was mild. 'Kurenainoyume' possesses a homozygous Md-ACS1-2 allele (Igarashi et al, 2011), which produces less ethylene and a firmer fruit than MdACS1-1/2 and MdACS1-1/1 genotypes (Oraguzie et al, 2007;Zhu and Barritt, 2008). This trait may have affected the results of the present study; 1-MCP treatment failed to show dramatic suppression of the internal ethylene production due to the genetic features.…”
Section: Effect Of 1-mcp Treatment On the Storability Of Bagged Fruitmentioning
confidence: 69%
“…The application of MAS to apple-breeding programs has mainly focused on certain well-known traits of interest, including resistance to scab, flavor, firmness, columnar growth habit, and skin color (Takos et al, 2006;Bus et al, 2007;Zhu and Barritt, 2008;Moriya et al, 2012). For the skin color trait, it has been shown that a RAPD DNA marker derived from the red skin gene, Rf, is able to discriminate between most red and non-red apple cultivars, and has been used in advanced breeding selections (Cheng et al, 1996).…”
Section: Introductionmentioning
confidence: 99%